To block or not to block—hormonal signaling in the treatment of cancers - Abikar, Apoorva; Saimon, Chriswin; Ranganathan, Prathibha (Frontiers in Endocrinology, 2023)
Breast and prostate glands are the two major organs which are highly dependent on the gonadal steroid hormones for their development and homeostasis. The cancers of these organs also show a large dependence on the steroid hormones, and that has formed the basis of endocrine therapy. Estrogen deprivation by oophorectomy was in active practice since 1970s and androgen deprivation therapy for prostate cancer was a major breakthrough in medicine in 1941. Since then, several improvisations have happened in these modes of therapy. However, development of resistance to this deprivation and emergence of hormone independence is a major problem in both cancers. Lessons learnt from rodent models, have made it clear that the male hormone has a role in females and the vice versa. Also, the metabolic products of these hormones may have unintentional effects including proliferative conditions in both the sexes. Hence administering estrogen as a method of chemical castration in males and administering DHT in females may not be the ideal scenario. It would be important to consider the status of the opposite sex hormone signalling and its effects and come up with a combinatorial regime to strike a balance between androgen and estrogen signalling. This review summarizes the current understanding and developments in this field in the context of prostate cancer.